Certificateless public auditing with data privacy preserving for cloud-based smart grid data - Gai, Chao; Shen, Wenting; Yang, Ming; Su, Ye (Frontiers in Energy Research, 2023)
As the promising next generation power system, smart grid can collect and analyze the grid information in real time, which greatly improves the reliability and efficiency of the grid. However, as smart grid coverage expands, more and more data is being collected. To store and manage the massive amount of smart grid data, the data owners choose to upload the grid data to the cloud for storage and regularly check the integrity of their data. However, traditional public auditing schemes are mostly based on Public Key Infrastructure (PKI) or Identity Based Cryptography (IBC) system, which will lead to complicated certificate management and inherent key escrow problems. We propose a certificateless public auditing scheme for cloud-based smart grid data, which can avoid the above two problems. In order to prevent the disclosure of the private data collected by the smart grid during the phase of auditing, we use the random masking technique to protect data privacy. The security analysis and the performance evaluation show the proposed scheme is secure and efficient.